PANSS‐6: a brief rating scale for the measurement of severity in schizophrenia. (12th November 2015) - Østergaard, S. D.; Lemming, O. M.; Mors, O.; Correll, C. U.; Bech, P.
Abstract : Objective: The 30‐item Positive and Negative Syndrome Scale (PANSS‐30) is the most widely used rating scale in schizophrenia, but too long for clinical use. Shorter PANSS versions have been proposed, including the PANSS‐14 and PANSS‐8. However, none of these PANSS versions has been validated using the parametric Rasch rating scale model, which evaluates 'scalability'. Scalability means that each item in a rating scale provides unique information regarding syndrome severity and is a statistical prerequisite for using the total score as a measure of overall severity. Method: Based on data from two randomized placebo‐controlled trials in schizophrenia, we tested the scalability of PANSS‐30, PANSS‐14 and PANSS‐8 by means of the parametric Rasch rating scale model. Furthermore, we tested whether a scalable PANSS version could separate efficacy of haloperidol and sertindole from placebo. Results: Neither PANSS‐30, PANSS‐14 nor PANSS‐8 was scalable. However, PANSS‐6, consisting of the items: P1‐Delusions, P2‐Conceptual disorganization, P3‐Hallucinations, N1‐Blunted Affect, N4‐Social withdrawal, N6‐Lack of spontaneity and flow of conversation, was scalable. Furthermore, PANSS‐6 captured superior symptom reduction and higher remission rates during treatment with haloperidol and sertindole vs. placebo. Conclusion: PANSS‐6 is a short schizophrenia severity rating scale that adequately separates antipsychotic efficacy from that of placebo.